(untitled) (Physical Education, Health and Social Sciences, 2026)
Teacher transfer is experienced globally and is on the rise despite the presence of transfer policies governing teachers’ mobility. Teachers’ transfer may either be voluntary or involuntary. The transfer of teachers is a significant aspect of educational management that helps address staffing needs while also considering the professional aspirations of educators. The objective of the current study was to explore the impact of frequent transfer of teachers on their performance at the primary level of tehsil Faisalabad Sadar. According to the latest data from the School Information System, there are 8 government boys’ primary school, 7 elementary boys’ schools and 8 government girls’ primary schools and 10 girls’ government elementary schools. So, in these 15 government boys’ schools, there are currently 99 teachers and in 18 government girls’ schools, 100 teachers were recruited. The population of the current study was 199 teachers of Markaz Miranwala. The sample size was 132 teachers (67 male and 66 female teachers) with a 95% confidence interval and a margin of error of 5%. The sample size was calculated through idsurvey.com/en/sample-size-calculator/#ssc. A proportionate sampling technique used to draw the proportion of male and female respondents among the total sample. A proportionate sampling technique was selected for the collection of data. In this survey, a questionnaire was used for the collection of quantitative data. After the collection of data, it was analyzed through Statistical Packages for Social Sciences (SPSS). It was concluded that teachers’ transfers were shown positive effect on new teacher recruitment. By creating vacancies and promoting equity within schools, transfers attracted qualified candidates and contributed to the diversification of the teaching staff. However, the study also pointed out that the frequent transfer of teachers could hinder the adaptation of new staff to educational trends, potentially leading to challenges in maintaining a stable and effective teaching force. It was suggested that educational department should offer career development programs to reduce teacher turnover. Public schools should improve job satisfaction through better work conditions and support. Teacher transfer policies should be flexible to accommodate personal and professional needs.